Urban Archaeology. How to represent uncertainty: the archaeological excavations of Piazza Bovio in Naples - Capone, Mara (DISEGNARECON, 2011)
The evolution of communication systems has led to experimentation with new ways to enjoying cultural heritage using digital media. Archaeological finding are only a piece of matter with high ambiguity level and so we have to do something to resolve this ambiguity. The use of 3D models can achieve the reconstruction of a digital copy, opening new perspectives in the context of archaeological research and posing new problems related to the identification of an appropriate code to represent the uncertainty. The choice of a particularly complex case study, the archaeological excavation of Piazza Bovio in Naples, allowed us to address a number of unusual issues and we have tried to tell the story of the place testing the use of 3D models in a film sequence.